Design of A Screw Conveyor in Palm Oil Mill Malaysia - TAN, JIA XIN (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Moving heavy goods, sharp items, raw materials, and mass-produced products are extremely helped by screw conveyor. During the process of dry separation of palm kernel mixture, there is a screw conveyor between the outlet of the cracking machine and inlet of winnowing column system, where the screw conveyor is used to convey the mixture of kernels and shells to the winnowing column system to carry out dry separation process. There is no standard design practice for engineer for designing purpose to design a proper screw conveyor for palm oil mills in Malaysia. The purpose of this project is to design a screw conveyor to convey the mixture of kernels and shells of palm fruits in dry separation process in palm oil mills. The design and analysis of screw conveyor is done to select appropriate components according to an assumed situation. Furthermore, this project also has to design a 3D model for screw conveyor to carry out appropriate analysis to have proper design of screw conveyor by generating the 3D model after designing the screw conveyor and selecting the components for screw conveyor. Additionally, the 3D model of screw conveyor is completed and analysed by using SolidWorks software to evaluate the product specification. The final design of screw conveyor is expected to convey the mixture of palm kernels and palm shell with an assumed capacity of 1000kg per hour.